The evolution of national referendum tools in Czech Republic and Slovakia’s comparative case - Ratto Trabucco, Fabio (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This article analyses and compares the direct democracy tools in the Czech Republic and Slovakia in the framework of the former socialist Central-Eastern European area. Based on comparison and the previous Czechoslovak Republic experience, the author draws conclusions about shortcomings of the legal framework of direct democracy in the Constitutions of both countries. However, the Czech and Slovak national referendum experiences since 1993 confirm a weak usage of these tools. The majority of politicians are unwilling to make use of the national referendum tools and to make further regulations of the legislation of the referendum tools. In both countries, except for the EU accession field, the national referendum tools have been virtually non-existent. Moreover, the national referendums are tools in the hands of the political parties systematically used by politicians to discredit the opposition political part. The resulting of these two factors is that the tool becomes a real parody of direct democracy.
Keywords: national referendum tools; Rule of law; people’s participation; Czech Republic; Slovakia